2018
DOI: 10.1523/jneurosci.2643-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

β-Secretase BACE1 Promotes Surface Expression and Function of Kv3.4 at Hippocampal Mossy Fiber Synapses

Abstract: The β-secretase β-site APP-cleaving enzyme 1 (BACE1) is deemed a major culprit in Alzheimer's disease, but accumulating evidence indicates that there is more to the enzyme than driving the amyloidogenic processing of the amyloid precursor protein. For example, BACE1 has emerged as an important regulator of neuronal activity through proteolytic and, most unexpectedly, also through nonproteolytic interactions with several ion channels. Here, we identify and characterize the voltage-gated K channel 3.4 (Kv3.4) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 68 publications
3
14
0
Order By: Relevance
“…[69][70][71][72][73] We have previously revealed the interaction of BACE1 with the voltage-gated sodium channel NaV1.2, voltage-gated potassium channel KV3.4, and potassium channels of the KCNQ family (KCNQ1-3), for which BACE1 acts as a non-proteolytic accessory subunit. 22,[74][75][76][77] Both NaV1.2 and KCNQ2/3 are anchored to the actin cytoskeleton at the axon initial segment by interaction with ankyrin-G. 78 A similar anchoring to actin has been described for KCNQ1 via the protein kinase A anchoring protein (AKAP) yotiao. 50,79 It is therefore conceivable that the restricted motility of BACE1 results, at least in part, from its physical association with anchored membrane proteins.…”
Section: Single Molecule Bace1 Diffusion Analysismentioning
confidence: 86%
“…[69][70][71][72][73] We have previously revealed the interaction of BACE1 with the voltage-gated sodium channel NaV1.2, voltage-gated potassium channel KV3.4, and potassium channels of the KCNQ family (KCNQ1-3), for which BACE1 acts as a non-proteolytic accessory subunit. 22,[74][75][76][77] Both NaV1.2 and KCNQ2/3 are anchored to the actin cytoskeleton at the axon initial segment by interaction with ankyrin-G. 78 A similar anchoring to actin has been described for KCNQ1 via the protein kinase A anchoring protein (AKAP) yotiao. 50,79 It is therefore conceivable that the restricted motility of BACE1 results, at least in part, from its physical association with anchored membrane proteins.…”
Section: Single Molecule Bace1 Diffusion Analysismentioning
confidence: 86%
“…of gray (Fig. 8A) (Shimshek et al, 2016;Hartmann et al, 2018). Western blot analysis of amyloid precursor protein (APP) and contactin-2 (CNTN2 (Gautam et al, 2014), two known BACE1 substrates, demonstrated a significant increase of the respective, unprocessed full-length protein (Fig.…”
Section: Treatment With Bace1 Inhibitor Does Not Cause Hearing Lossmentioning
confidence: 99%
“…20 This pathway is widely regarded as the primary pathogenic mechanism in Alzheimer's disease. 24 According to studies, elevated levels of BACE1 in the CSF are noticeable in the later stages of sporadic Alzheimer's disease. This is due to the association of the BACE1 level with the level of amyloidogenesis and the intensity of axon degradation.…”
Section: Cerebrospinal Fluid Biomarkersmentioning
confidence: 99%